Microwave‐assisted extraction and ultrasound‐assisted extraction for recovering carotenoids from Gac peel and their effects on antioxidant capacity of the extracts - Chuyen, Hoang V. (Food Sci Nutr, 2017)
The peel of Gac fruit (Momordica cochinchinensis Spreng.) contains high levels of bioactive compounds, especially carotenoids which possess significant antioxidant capacities. However, the peel of Gac is regarded as a waste from the production of carotenoid‐rich oil from Gac fruit. In this study, carotenoids of Gac peel were extracted by microwave‐assisted extraction (MAE) and ultrasound‐assisted extraction (UAE) using ethyl acetate as extraction solvent. The effect of extraction time and different levels of microwave and ultrasonic powers on the yield of total carotenoid and antioxidant capacity of the extracts were investigated. The results showed that an extraction at 120 W for 25 min and an extraction at 200 W for 80 min were the most effective for MAE and UAE of the Gac peel samples, respectively. The maximum carotenoid and antioxidant capacity yields of UAE were significantly higher than those of the MAE. The antioxidant capacity of extract obtained by the UAE was also significantly higher that of the conventional extraction using the same ratio of solvent to material. The results showed that both MAE and UAE could be used to reduce the extraction time significantly in comparison with conventional extraction of Gac peel while still obtained good extraction efficiencies. Thus, MAE and UAE are recommended for the improvement of carotenoid and antioxidant capacity extraction from Gac peel.